Determining Effective Length for 40 HM-T Steel by Use of Non-Local Line Method Concept - Robak Grzegorz (Polish Maritime Research, 2018)
In the paper, the concept of non-local line method is presented and used for determining the effective length for notched elements. Experimental tests and calculations were performed for 40 HM-T (42CrMo4+QT) steel made specimens of two types, i.e. smooth specimens, and notched specimens with notch radius equal to 0.2 mm, 0.5 mm, 0.8 mm, and 1 mm. The performed FEM calculations took into account the multi-linear hardening model and cyclic material properties. The concept of the presented non-local line method bases on finding the position of critical plane and determining the effective length, meant as the fracture process zone. During numerical stress gradient simulations, also the weight function was implemented. It was observed that the effective length increases as the load increases.